Do environmental quality and policy changes affect the evolution of consumers’ intentions to buy new energy vehicles - Lin, Boqiang; Shi, Lei (Applied energy, 2022)
•We explored the evolution of consumers' intentions to purchase new energy vehicles.•Consumers’ intentions to purchase NEVs first declined and then increased.•The inconsistency of consumers’ purchasing intention become more evident over time.•Although consumers’ cognition of the role of new energy vehicles in environmental governance is biased, it improves consumers’ purchase intention at all stages. The decision-making process of car purchase tends to last relatively longer which makes consumers' intention to purchase new energy vehicle may affected by various factors and significantly change. For the first time, we divide consumers’ intention to buy new energy vehicles into three stages, early intention and later intention in the decision-making process and future intention, and then extend the influencing relationships that have been verified from the study of future purchasing intention into these stages. This provides a new perspective for an in-depth understanding of the evolution process and the influence mechanism of purchasing new energy vehicles. Specifically, we collect a data set including 2,565 families with cars and then use the partial least squares structural equation model, to verify the theoretical model. The results show that our model has universal applicability to samples from different regions, indicating that it is stable and can be applied to other regions and countries. Consumers’ willingness to purchase new energy vehicles shows a decreasing trend in the early stages and then rises in the subsequent stages. Although consumers’ cognition of the role of new energy vehicles in environmental governance is biased, it improves consumers’ purchase intention at all stages. Finally, some corresponding policy measures are put forward to promote the further development of new energy vehicles.